Gold-core silica shell nanoparticles application in imaging and therapy: A review - Moreira, André Ferreira (2018)
Nanomaterials have assumed a prominent role in biomedical field during the past years. Particularly, the gold-core silica shell nanoparticles present unique physical and chemical properties that make nanodevices appealing for theragnostic applications. The gold core characteristic X-ray attenuation, surface enhanced raman scattering and tunable absorption in the near-infrared region supports the applicability of these systems in X-ray, photoacoustic and thermal imaging as well as in photothermal and photodynamic based therapies. Additionally, the inclusion of the silica shell stabilizes the gold core, protecting it from premature degradation and aggregation, and also provides additional cargo capacity for therapeutic molecules. Further, both silica and gold are described as biocompatible, inert and nontoxic materials. In this review, an overview of the gold core-silica shell nanoparticles applications in nanomedicine is provided, highlighting the different particle shapes and their application in bioimaging and therapy. Further, the basics of the gold core-silica shell nanoparticles synthesis procedures, general properties, and biosafety are also described.